(untitled) (Mongolian Journal of Agricultural Sciences, 2022)
Animals, especially birds cause yield loss that is substantial burden on farmers Therefore, the laser scarecrow bird repellant equipment was constructed with purpose to reduce sea buckthorn yield loss caused by bird and field tested. The preliminary results that support that use of bird repellent would retain the harvesting yield of sea buckthorn and could be used further in farming areas.